2018
DOI: 10.7759/cureus.3217
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Physical Activity in Young Adults and Stroke: Was It Due to My Job?

Abstract: The association of physical activity and stroke among working young adults and vice versa has increasingly empathized in recent years. Lack of physical activity, along with many other modifiable risk factors, such as hypertension, obesity, atherosclerosis, and diabetes, contributes through vascular dysfunction to the development of adverse cerebrovascular events in the future and has always been a topic of interest in the fields of neurology and stroke rehabilitation. We wrote this review article to elaborate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…218 It was also demonstrated that both Ga-and Sn-PPIXs inhibit growth of Mycobacterium abscessus. 154,219 Additionally, in M. abscessus-infected macrophages, treatment with MPPs inhibited mycobacterial growth but did not exhibit toxicity towards host macrophages. Moreover, 1 μM GaPPIX inhibited intracellular M. abscessus growth to a level significantly greater than 25 μM Ga(NO 3 ) 3 ,…”
Section: Targeting Heme Uptake Pathwaysmentioning
confidence: 97%
See 1 more Smart Citation
“…218 It was also demonstrated that both Ga-and Sn-PPIXs inhibit growth of Mycobacterium abscessus. 154,219 Additionally, in M. abscessus-infected macrophages, treatment with MPPs inhibited mycobacterial growth but did not exhibit toxicity towards host macrophages. Moreover, 1 μM GaPPIX inhibited intracellular M. abscessus growth to a level significantly greater than 25 μM Ga(NO 3 ) 3 ,…”
Section: Targeting Heme Uptake Pathwaysmentioning
confidence: 97%
“…Both are proposed to be involved in heme uptake and are also required for the export of important Mtb cell-wall lipids, including mycolic acids. 90,[154][155][156][157][158] There are no X-ray structures of full-length MmpL3 or MmpL11, however, a structure exists for the D2 soluble domain from MmpL11, Figure 15B. 92 The MmpL11 D2 structure consists of two anti-parallel α-helices situated above the antiparallel β-sheet forming a βαββαβ fold similar to RND porter subdomains, Figure 15B.…”
Section: (Ii) Role Of Rv0203mentioning
confidence: 99%
“…They demonstrated that individuals with low physically active occupations are more prone to develop a stroke as compared to workers who have a moderate amount of PA in their jobs. 53 The second reason for this separate time window was the gender-specific imbalance with regard to housework and shopping, which was very often reported in the personal conversations about typical daily routines. It is known that even in addition to their occupation, females however engage in domestic activities more (1,42) = 4.247, p = 0.046* F (1,42) = 3.848, p = 0.056…”
Section: Pa Levels In Patients and Their Spousesmentioning
confidence: 99%
“…The hypothesis of the present cross-sectional study, about high intensity of OPA could be associated with a detrimental in health status, in particular, in cardiovascular health [13]; and it is con rmed in female employees, due to negative association with blood pressure levels. A possible explanation in females cleaners, who in present study females represented the majority of type of job, the muscle contractions during manual handling could be associated with elevated blood pressures [13].…”
Section: Resultsmentioning
confidence: 63%